Downregulation of WW domain-containing oxidoreductase leads to tamoxifen-resistance by the inactivation of Hippo signaling. Issue 12 (September 2019) - Li, Juan; Feng, Xuefei; Li, Canyu; Liu, Jie; Li, Pingping; Wang, Ruiqi; Chen, He; Liu, Peijun
Acquired tamoxifen-resistance is an important cause of death in patients with hormone-dependent breast tumors. Therefore, understanding the molecular mechanisms underlying the development of tamoxifen-resistance is critical for successful endocrine therapy. This study aimed to define the role of WW domain-containing oxidoreductase (WWOX) in acquired tamoxifen-resistance. Our results show that low WWOX expression was significantly related to tamoxifen-resistance. Moreover, WWOX-knockdown increased resistance to tamoxifen, while WWOX overexpression decreased the resistance. Furthermore, WWOX silencing decreased Yes-associated protein (YAP) phosphorylation and increased YAP nuclear translocation. Finally, YAP silencing decreased tamoxifen-resistance in WWOX-knockdown cells. Our findings demonstrate that WWOX downregulation can lead to the development of tamoxifen-resistance by inactivating Hippo signaling. Thus, WWOX might be a valuable target and prognostic marker for tamoxifen-resistance. Impact statement: Understanding the molecular pathways leading to the development of tamoxifen-resistance is an important research focus as acquired tamoxifen-resistance is the main cause of death in patients with benign primary prognosis. Although WW domain-containing oxidoreductase (WWOX) has been related to breast tumorigenesis, its role in acquired tamoxifen-resistance has not yet been demonstrated. Our findings show that WWOX might be a valuable therapeutic target and prognostic marker for tamoxifen-resistance.